Pure and Simple Politics : the American Federation of Labor and Political Activism, 1881-1917. - Greene, Julie (Cambridge University Press, 1998)
This study explores the political evolution of the US labor movement, focusing on its dominant organization, the American Federation of Labor, during a key period (1881 to 1917) of transformation in US political history.